Direct conversion of methane into methanol - Burch, R; Squire, G; Tsang, S (1989)
The direct oxidation of methane into methanol has been studied in a flow microreactor. The effects, on the selectivity to methanol, of the type of reactor, temperature, pressure, residence time, oxygen content, gas mixing and dilution, have been investigated. The results show that at relatively low pressures the use of metallic reactors and/or catalysts leads to the formation of complete oxidation products. However, at higher pressures none of the experimental parameters studied has a significant influence on the selectivity to methanol, which in all cases is ca. 40 %, much lower than claimed in recent publications. Investigations of the stability of methanol at high temperatures and pressures in the presence of oxygen show that loss of methanol through further oxidation is unimportant except in the presence of metals such as Cu. In the presence of methane and oxygen some methanol is destroyed, and this is attributed to reactions involving methyl radicals produced during the activation of methane by oxygen. However, this loss of methanol is insufficient to account for the low overall selectivity observed. It is concluded that the detailed design of the reactor may be of critical importance in obtaining high methanol yields.